Integration of Artificial Intelligence in PAI Material Development: Analysis of Learning Effectiveness and Interaction - Muhammad, Muhammad; Wahab, Wahab (STAI Syaichona Moh. Cholil Bangkalan, 2025)
The research aims to examine the literature on applying artificial intelligence (AI) in Islamic Religious Education (PAI) materials to evaluate its effectiveness in enhancing interaction and learning quality. This literature review explores how AI can facilitate interactive and adaptive learning experiences tailored to students' needs while strengthening the overall effectiveness of PAI instruction. This study employs a qualitative approach through a literature review, analyzing 30 sources from the past decade (2014–2024) related to educational technology, AI implementation, and PAI teaching materials. Previous research indicates that AI in PAI materials can personalize learning, provide real-time feedback, and improve student engagement with the content. However, AI may also reduce interpersonal interaction in religious discussions. Therefore, integrating AI with discussion-based learning is recommended for optimal outcomes. The development of AI-based PAI materials has the potential to enhance learning effectiveness and foster more dynamic interactions in the digital era. Academically, the research emphasizes the significance of hybrid learning that combines AI with active learning methods and underscores the need to balance technology with teacher-student interaction in education.